High-level synthesis algorithms with floorplaning for distributed/shared-register architectures - Ohchi, A.; Togawa, N.; Yanagisawa, M.; Ohtsuki, T. (2008 International Symposiium on VLSI Design, Automation and Test, 2008)
In this paper, we propose a high-level synthesis method targeting distributed/shared-register architectures. Our method repeats (1) scheduling/FU binding, (2) register allocation, (3) register binding, and (4) module placement. By feeding back floorplan information from (4) to (1), our method obtains a distributed/shared-register architecture where its scheduling/binding as well as floorplanning are simultaneously optimized. Experimental results show that the area is decreased by 13.6% while maintaining the performance of the circuit equal with that using distributed-register architectures.